An unusual case of Shone's complex in an adult depicted on computed tomography angiography. Issue 8 (1st June 2021) - Verma, Mansi; Chavhan, Rahul; Kumar, Sanjeev; Seth, Sandeep
Abstract: We present a case of a 22‐year‐old male with dyspnea on exertion where computed tomography revealed complete Shone's complex. This case highlights the complementary role of computed tomography in the anatomical evaluation of patients with complex heart diseases.